Palliative care for patients with glioma: A recent scientometric analysis of the Web of Science in 2022 - Xiao, Zhiyuan; Chen, Wenlin; Zhao, Haiyan; Wang, Hai; Zhao, Binghao; Liu, Delin; Yang, Tianrui; Liang, Tingyu; Xing, Hao; Wang, Yaning; Wang, Yuekun; Guo, Xiaopeng; et al. (Frontiers in Oncology, 2022)
Background Patients with glioma present with complex palliative care needs throughout their disease trajectory. A scientometric analysis is effective and widely used to summarize the most influential studies within a certain field. We present the first scientometric analysis of palliative care for patients with glioma. Methods Based on a Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) principle, we conducted a generalized search for articles on palliative care for glioma in the Web of Science database and evaluated the top 100 most frequently cited articles among 2,542 articles. Results The number of citations for the top 100 cited articles on palliative care for glioma ranged from 10 to 223. We have a narrative conclusion, as follows: most of these articles were published in oncology-specific journals (n = 53) and palliative-specific journals (n = 22). The United States, Australia, and the Netherlands were the top three countries contributing most of the articles (n = 59). Most of the research methods were quantitative analyses, qualitative analyses, and systematic reviews and meta-analyses (n = 70). In quantitative studies, 66 scales were used, and the top three scales used included the following: the Distress Thermometer, Functional Assessment of Cancer Therapy-Brain Index (FACT-Br), and Karnofsky Performance Scale (KPS). The articles were classified into six major categories based on research subjects, including patients (n = 44), caregivers (n = 16), patients and caregivers (n = 20), literature (n = 19), and healthcare providers (n = 1). Articles were classified into seven major categories based on research themes: quality of life (n = 11); end-of-life symptoms and care (n = 16); palliative and supportive care needs (n = 35); advance care planning and decision making (n = 4); psychological, social, and spiritual needs (n = 12); hospice utilization and referral (n = 3); and others (n = 19). The studies of the primary topic are correlated with the number of citations. Conclusions The results of the analysis indicated that patients diagnosed with glioma present a high variety of palliative care needs, including physical, psychological, social, and spiritual needs. The caregiver’s burden and needs are important as well. The proportion of quantitative analyses, qualitative analyses, and systematic reviews and meta-analyses is relatively high, but the number of randomized controlled trials (RCTs) was low. End-of-life care and supportive care needs appeared frequently. Thus, palliative care is an urgent need to be addressed in glioma management. The appropriate scales should be selected for patients with glioma and meet their palliative needs.